2022
DOI: 10.20525/ijrbs.v11i10.2185
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between previous leadership theories and ethical leadership in a South African context: a narrative review

Abstract: Leadership theories have underpinned significant leadership studies and practices which span decades. Despite the plethora of research on different leadership theories and styles, there is minimal research exploring the relationship between previous leadership theories and the ethical leadership style. Previous research has shown that the ethical leadership effect goes above and beyond other leadership styles and theories as the latter lack an exclusive ethical focus. Therefore, this paper aims to address the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the context of fostering inclusivity and empowerment for individuals with physical challenges through ethical leadership and community engagement in underserved areas in the U.S., it is essential to draw upon the philosophical foundations of ethical leadership. Ethical leadership encompasses inspiring, encouraging, and visionary aspects that empower individuals (Bhana & Suknunan, 2022). This form of leadership is deeply rooted in ethical behavior, which has historical significance in ancient Greek philosophy and major world religions (Zyl, 2015).…”
Section: Previous Studiesmentioning
confidence: 99%
“…In the context of fostering inclusivity and empowerment for individuals with physical challenges through ethical leadership and community engagement in underserved areas in the U.S., it is essential to draw upon the philosophical foundations of ethical leadership. Ethical leadership encompasses inspiring, encouraging, and visionary aspects that empower individuals (Bhana & Suknunan, 2022). This form of leadership is deeply rooted in ethical behavior, which has historical significance in ancient Greek philosophy and major world religions (Zyl, 2015).…”
Section: Previous Studiesmentioning
confidence: 99%
“…In addition, eastern ideology further provided the support to African states, and this solidified their relationship which was filled with moral virtue while allowing African states to subscribe to their own ideas especially from an African philosophy point of view. This is important as moral virtue cements the ubuntu from the Ngunu language meaning "umuntu ngumuntu ngabantu" or, in Sesotho, "motho ke motho ka batho", meaning a person is a person through other people (Bhana, & Suknunan, 2022). Hlongwane et al (2019: 62) further alluded to how this idea can be found in the practical, mythical, spiritual and cosmological origins of ancient Egyptian concept of 'Ma at'.…”
Section: Ubuntu and African Philosophy On The Ukraine-russian Warmentioning
confidence: 99%